Strategi Penggunaan WhatsApp sebagai Customer Relations pada Proses Penerimaan Mahasiswa Baru Universitas Tarumanagara - Caesar Oei Winka, Wynne; Junaidi, Ahmad (Kiwari, 2024)
Communication is the main aspect of social life so that this activity is not just exchanging messages but to achieve common meaning. As we know, communication activities are currently influenced by various factors, namely the development of technology and human resources. The use of technology is also carried out by Tarumanagara University to disseminate information and handle complaints related to the admission process for new students through WhatsApp social media. In this study, the author realized that in implementing communication strategies, persuasion skills are needed to convey stimulus (messages) so that they can achieve the desired response. The theories used in this study are interpersonal communication theory, communication strategies and persuasion influenced by new media. The research uses a descriptive qualitative approach with a case study research method, research data obtained from the results of in-depth interviews, participatory observations, documentation, and literature studies of four speakers. The results showed that the use of WhatsApp media as a strategy in reaching prospective students was quite good. This study also included evidence of support in the form of survey results conducted every month specifically for admission services via WhatsApp with an average result in 2022 obtaining a value of 3.8-4.0 for WhatsApp services at Tarumanagara University Admissions. Komunikasi menjadi aspek utama dalam kehidupan bermasyarakat sehingga kegiatan ini bukanlah sekadar bertukar pesan saja melainkan untuk mencapai kesamaan makna. Seperti yang kita ketahui kegiatan komunikasi saat ini dipengaruhi dengan berbagai faktor yakni perkembangan teknologi dan sumber daya manusia. Pemanfaatan teknologi juga dilakukan oleh Universitas Tarumanagara untuk menyebarkan informasi serta menangani keluhan terkait proses penerimaan Mahasiswa baru melalui media sosial WhatsApp. Pada penelitian ini penulis menyadari bahwa dalam menerapkan strategi komunikasi diperlukan kemampuan persuasi untuk menyampaikan stimulus (pesan) sehingga dapat mencapai respon yang diinginkan. Teori yang digunakan dalam penelitian ini adalah teori Komunikasi Antarpribadi, Strategi Komunikasi, dan Persuasi yang dipengaruhi oleh New Media. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode penelitian studi kasus, data hasil penelitian diperoleh dari hasil wawancara mendalam, observasi partisipatif, dokumentasi, dan studi kepustakaan terhadap empat narasumber. Hasil penelitian menunjukan bahwa pemanfaat media WhatsApp sebagai strategi dalam menjangkau calon mahasiswa sudah cukup baik. Pada penelitian ini juga disertakan bukti dukungan berupa hasil survei yang dilakukan setiap bulan khusus untuk pelayanan Admisi via WhatsApp dengan hasil rata-rata di tahun 2022 memperoleh nilai 3.8-4.0 untuk layanan WhatsApp di Admisi Universitas Tarumanagara.